A novel approach for damage quantification using the dynamic response of a metallic beam under thermo-mechanical loads - Zai, Behzad Ahmed; Khan, Muhammad A.; Khan, Kamran Ahmed; Mansoor, Asif (Elsevier, 2019)
This paper investigates the interdependencies of crack depth and crack location on the dynamic response of a cantilever beam under thermo-mechanical loads. Temperature can influence the stiffness of the structure, thus, the change in stiffness can lead to variation in frequency, damping and amplitude response. These variations are used as key parameters to quantify damage of Aluminum 2024 specimen under thermo-mechanical loads. Experiments are performed on cantilever beams at non-heating (room temperature) and elevated temperature, i.e., 50 °C, 100 °C, 150 °C and 200 °C. This study considers a cantilever beam having various initially seeded crack depth and locations. The analytical, numerical and experimental results for all configurations are found in good agreement. Dynamic response formulation is presented experimentally on beam for the first time under thermo-mechanical loads. Using available experimental data, a novel tool is formulated for in-situ damage assessment in the metallic structures. This tool can quantify and locate damage using the dynamic response and temperature including the diagnosis of subsurface cracking. The obtained results demonstrate the possibility to diagnose the crack growth at any instant within the operational condition under thermo-mechanical loads.
Keywords: Crack depth; Dynamic response; Thermo-mechanical loads; Crack prorogation; Crack location